Characteristics of Malaysian highly cited papers - Abdullah, Noorhidawati; Mohd Khalid, Yanti Idaya Aspura; Mohd Nor, Zahila; Abdullah, Abrizah (Universiti Malaya (UM), 2017)
Highly cited papers serve as a proxy for excellence. In this paper, we identify Malaysia's highly-cited papers and explore the characteristics of these papers. The research question posed is "What characterizes Malaysian highly cited papers?" This study adopts the definition by Thomson Reuters Essential Science Indicator, i.e. the highly cited papers are papers that received enough citations to be placed in the top 1 percent of the academic field of each 22 subject areas based on a highly cited threshold for the field and publication year. As a small scientific nation, Malaysia has a rather limited number of papers being highly cited, and we observed nine characteristics of highly cited papers based on 708 datasets obtained from the Web of Science. Malaysian highly cited papers are largely represented by articles, but reviews have higher impact. Typically, these papers have a low self-cited index and they are published in the First Quartile of the science discipline publications. The papers are mainly the outcome of national funded research; involve multiple co-authorship and international collaboration; affiliated to Malaysian research universities and Malaysian authors often play a dominant role as first or reprint authors. Partnership with scientists from Iran, Australia and UK may increase markedly the possibility of a Malaysian paper becoming highly cited. This investigation has shown that these are the characteristics of Malaysian highly cited papers, but to what extent can these be used as indicators need further investigation and discussions among the scientific community.